The inviolability of medical confidentiality in Malaysia: an analysis of the rules and exceptions - Jahn Kassim, Puteri Nemie; Ramli, Nazri (Ahmad Ibrahim Kulliyyah of Law International Islamic University Malaysia, 2016)
The duty of medical confidentiality has been one of the core duties of medical practice as information created, disclosed, acquired directly or indirectly during the doctor-patient relationship is considered confidential and requires legitimate protection. Further, preserving confidentiality on the premise that the relationship between doctor and patient has been built on trust and confidence renders the duty to be seen as sacrosanct. The source for this duty can be found not only in the Hippocratic Oath, codes of ethics, religious tenets but also in the common law, principles of equity and statutory provisions. Nevertheless, technological advancements and the growth of social networks have contributed to the difficulties in preserving confidentiality as the information gathered tends to become vulnerable in unsecure environments. However, the duty of medical confidentiality is by no means absolute as it can be breached in situations in which there are stronger conflicting duties. This article discusses the rules governing the duty of medical confidentiality and the exceptions in which infringements to this duty become justified. It also gives an overview of the duty of confidentiality under Islamic law. It concludes that the inviolability of this duty may be without doubt but circumstances warranting its disclosure are crucial to serve the interests of justice.